Respuesta :
Answer:
a = -5
b = -1
m = -1
Step-by-step explanation:
Piecewise function:
f(x)= -5, x=0
f(x)= −x^2+3x+a, 0<x<2
f(x)= mx + b 2≤x≤3
The mean value theorem is applicable if f(x) is continuous on the entire closed interval [0;3] and differentiable on the entire closed interval [0;3].
To satisfied that at x = 0 :
−x^2+3x+a = -5
Then, a = -5
Derivative of −x^2+3x-5 is -2x + 3 and derivative of mx + b is m, at x = 2:
-2(2) + 3 = m
-1 = m
Replacing the functions at x = 2 :
−x^2+3x-5 = -x + b
−(2)^2+3*2-5 = -2 + b
-3 + 2 = b
-1 = b
The value of a is -5,m is -1 and b=-1
We have given that,
[tex]f(x)= -x^{2} +3x+a, 0 < x < 2[/tex]
What is the meaning of Piece wise function?
A function which is defined by multiple sub-functions, each sub-function applying to a certain interval of the main function's domain
[tex]f(x)= -5, x=0[/tex]
[tex]f(x)= -x^{2} +3x+a, 0 < x < 2[/tex]
[tex]f(x)= mx + b ... 2\leq x\leq 3[/tex]
Now by using the mean value theorem If f(x) is continuous on the entire closed interval [0,3] and differentiable on the entire closed interval [0,3].
To satisfied that at x = 0
[tex]-x^{2} +3x+a = -5[/tex]
Then, a = -5
Find the derivative of f(x)
[tex]\frac{d}{dx}(-x^{2} +3x-5)=-2x+3[/tex]
and derivative of [tex]mx + b[/tex] is m, at x = 2
Therefore we get,
-2(2) + 3 = m
-1 = m
Replacing x by 2 in the functions
[tex]-x^{2} +3x-5 = -x + b[/tex]
[tex]-2^{2} +3*2-5 = -2 + b[/tex]
[tex]-3 + 2 = b[/tex]
[tex]-1 = b[/tex]
Therefore, the value of a=-5,m=-1 and b=-1
to learn more about the piece wise function visit:
https://brainly.com/question/17883600